PENGARUH STRATEGI PROMOSI TERHADAP KEPUASAN KONSUMEN (Kasus Penjualan Jasa Akomodasi Hotel Comfort Dumai) - Purba, Dewi Wiswanti; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to know the effect of the promotion strategy on consumer satisfaction (case sales Dumai comfort hotel accommodation services).The data used are primary data and secondary data. sub-variables under study consists of advertising, personal selling, sales promotion, publicity, direct marketing. The analysis used is descriptive analysis and simple linear regression analysis using SPSS version 17. Sampling was performed by the method of accidental sampling with a sample size of 100 respondents.Results of research conducted by a simple linear regression analysis obtained coefficient value of 0.799, which that any changes in the independent variables promotion strategy will affect the dependent variable customer satisfaction. Based on these results it can be concluded that the value of the correlation coefficient has a value that is strong, it means that there is the influence of promotional strategy on customer satisfaction.Keywords: Promotion Strategy and Customer Satisfaction.